Digitalization Management in Schools : A Strategic Framework for Enhancing Academic Quality - Marginingsih, Peni; Kusumaningsih, Widya; Violinda, Qristin (Jurnal Paedagogy, 2025)
This study aims to analyze the planning, organization, implementation, andÂ  evaluation of school digitalization to improve academic quality at SMAN 1 Karangrayung, Central Java. This study uses a qualitative approach using observation, interview and documentation methods for data collection. The informants selected with a total of 23 people consisting of the Principal, Vice Principal, Teachers and Students.The data analysis technique in this study uses qualitative descriptive. Based on the results of the study, the management of school digitalization at SMA Negeri 1 Karangrayung has been running well in improving academic quality, covering aspects of planning, organizing, implementing, and evaluating. In planning, the school has formulated digitalization objectives, identified problems, collected relevant data, determined implementation stages, and formulated problem solving, including in terms of infrastructure, teacher training, data security, and program sustainability. Organization is carried out with a clear division of labor, the formation of a digitalization team, and routine coordination through periodic meetings to ensure smooth implementation. At the implementation stage, the school sets an implementation schedule, provides examples of technology applications, motivates teachers, communicates tasks well, and carries out ongoing coaching so that the digitalization program runs optimally. Evaluation is carried out by determining supervision standards, measuring teacher performance, comparing implementation results with established standards, and making continuous improvements. Overall, a systematic approach to school digitalization management has supported the improvement of academic quality and learning effectiveness at SMA Negeri 1 Karangrayung.